KNEE STRETCHING EXERCISE MENINGKATKAN PENCAPAIAN RANGE OF MOTION DAN MENURUNKAN TINGKAT NYERI PADA PASIEN ARTHRITIS RHEUMATOID - Putu Wira Kusuma Putra; Komang Widama Atmaja; Adi Sastrawan (Universitas Muhammadiyah Kudus, 2021)
Rheumatoid arthritis (AR) is one of the joint diseases commonly experienced by people with complaints of pain and limited range of joint motion. Management for patients who experience joint stiffness and pain can be done through exercise. Knee streecing exercise (KSE) is an activity of stretching the muscles in the knee area to increase muscle flexibility and range of joint motion. The purpose of this study was to determine the effect of giving Knee Stretching Exercise (KSE) on achieving range of motion (ROM) and Pain Intensity in Rheumatoid Arthritis Patients. This research design is quantitative with pre-experimental design using one group pretest and posttest design approach. The sample in this study were 45 elderly who suffer from rheumatoid arthritis (RA) according to inclusion and exclusion criteria. The instruments used in this study were the gionometer and numerical rating scale (NRS). Data were analyzed using the Wilcoxon rank test. Statistical test results showed that there was an effect of Knee Stretching Exercise (KSE) on the intensity of Pain and Achievement of Range of Motion in Reumathoid Athritis patients with a p value of 0.0001 (p 0.05). A decrease in the intensity of pain experienced by respondents after being given KSE training. The range of joint motion in the respondents increased to full flexion (1350) and full extension (0-10). It is suggested that the community routinely conduct KSE training because it is easy and simple to do. Keyword : Knee streecing exercise (KSE); range of motion; pain intensity